2016
DOI: 10.1001/jamaoncol.2015.3670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adverse Events for Endoscopic vs Percutaneous Biliary Drainage in the Treatment of Malignant Biliary Tract Obstruction in an Inpatient National Cohort

Abstract: Our results support the finding that endoscopic biliary drainage for malignant biliary obstruction is a first-line intervention. Endoscopic drainage is superior to percutaneous drainage, in regard to adverse event rate, for patients with pancreatic cancer. For patients with cholangiocarcinoma, endoscopic drainage is superior in centers that perform a low volume of percutaneous biliary drainage procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 13 publications
(19 reference statements)
1
94
0
1
Order By: Relevance
“…However, percutaneous drainage is associated with higher morbidity than ERCP and is not recommended in case of ascites and massive one-sided tumor involvement, thus sometimes restricting available access routes. 810 The other alternative interventional option of enteroscopy-guided retrograde drainage is poorly attractive since papillary access is successful in only 60–70% of patients, is very time-consuming and has few drainage options for advanced strictures as a consequence of small scope working channel and fewer ancillary devices to conduct complex procedures. 4 It was therefore interesting to investigate to what extent EUBD could provide jaundice relief even when limited to the left liver lobe, with the knowledge acquired from ERCP studies showing that in selected cases one-sided ERCP drainage of advanced hilar strictures could be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, percutaneous drainage is associated with higher morbidity than ERCP and is not recommended in case of ascites and massive one-sided tumor involvement, thus sometimes restricting available access routes. 810 The other alternative interventional option of enteroscopy-guided retrograde drainage is poorly attractive since papillary access is successful in only 60–70% of patients, is very time-consuming and has few drainage options for advanced strictures as a consequence of small scope working channel and fewer ancillary devices to conduct complex procedures. 4 It was therefore interesting to investigate to what extent EUBD could provide jaundice relief even when limited to the left liver lobe, with the knowledge acquired from ERCP studies showing that in selected cases one-sided ERCP drainage of advanced hilar strictures could be efficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, endoscopic retrograde cholangiopancreatography is not always an available option depending on the patient's comorbidities and the location of the tumor. In these cases, percutaneous biliary stent placement can be used with good success for biliary drainage (6)(7)(8)(9). Metal stents have been shown to be superior to plastic stents because of longer patency, a lower reintervention rate, and a reduced overall cost for palliative care of patients with inoperable tumors (10).…”
mentioning
confidence: 99%
“…While a growing body of literature, including randomized controlled trials and "real world" cohort studies, have shown that endoscopic biliary drainage is associated with lower adverse events, shorter length of hospitalization, lower costs, and better quality of life scores, our study demonstrates that disparities in access to ERCP across racial/ethnic and geographic cohorts remain. 6,7 Further studies are needed to determine if these differences are related to accessibility of treatment, local expertise, or regional practice variations in an effort to bridge the gap in care among pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) plays a critical role in the management of obstructive jaundice among pancreatic cancer patients. When compared to other biliary decompression interventions, such as percutaneous transhepatic biliary drainage (PTBD) or surgical biliary bypass (SBB), ERCP is associated with fewer adverse events, shorter length of stay, decreased hospital costs, and improved quality of life scores . Studies appraising the utilization of biliary decompression interventions can inform strategies to increase ERCP access and appropriate utilization.…”
Section: Introductionmentioning
confidence: 99%